Pengaruh Kompetensi, Beban Kerja Dan Kompensasi Terhadap Kinerja Pegawai Di Unit Pengelola Penanaman Modal Dan Pelayanan Terpadu Satu Pintu Kecamatan Menteng Provinsi DKI Jakarta - Akbar Wahdini Haikal; Ahmad Hidayat (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to analyze the effect of competence, workload and compensation on employee performance in Investment Management Unit and One-Stop Service in Menteng Regency, DKI Jakarta Province. This research method uses a quantitative approach. The sample in this study were 40 respondents using the saturated sampling technique or census method, then processed with multiple regression analysis. The results of this study indicate that competence affects employee performance based on the t value of 7.684> t table 2.024 and a coefficient of influence of 0.637; workload affects employee performance with a t value of 2.119> t table 2.024 and a regression coefficient of 0.288; furthermore, compensation affects employee performance with a t value of 2.577> t table 2.024 and a regression coefficient of 0.233. Based on the results of the simultaneous test, the joint influence of each independent variable on the employee performance variable shows positive and significant results with an F value of 50.717> F table of 2.63 and the contribution of competence, workload and compensation to employee performance based on the determinant value of adjust R square of 79.3%.